Proposed interpretive criteria and quality control parameters for ofloxacin susceptibility testing of Neisseria gonorrhoeae. - Fuchs, P C (1992)
A multilaboratory study designed to determine the in vitro susceptibility criteria and quality control parameters for ofloxacin against Neisseria gonorrhoeae was conducted according to the guidelines of the National Committee for Clinical Laboratory Standards. Proposed susceptibility breakpoints are MICs of less than or equal to 0.25 microgram/ml for the agar dilution test and greater than or equal to 31 mm for the disk diffusion test. A category for resistance could not be defined. Proposed acceptable quality control MICs for N. gonorrhoeae ATCC 49226 and Staphylococcus aureus ATCC 29213 range from 0.004 to 0.03 microgram/ml and 0.25 to 1.0 microgram/ml, respectively. With 5-micrograms ofloxacin disks, acceptable inhibitory zone diameters for S. aureus ATCC 25923 and the N. gonorrhoeae control strains range from 22 to 27 mm and 43 to 51 mm, respectively.